SPEAKING ANXIETY LEVEL OF EFL STUDENTS AT TENTH GRADE OF SENIOR HIGH SCHOOL 2 LUBUK SIKAPING - Yola Ariani; Eliza Eliza; Merry Prima Dewi (ELP (Journal of English Language Pedagogy), 2020)
This research has been done because the researcher found some problems in speaking at the tenth grade at SMAN 2 Lubuk Sikaping. The first problem was the students nervous when they were asked to speak up. The second problem was the students had lack of confidence. The third problem was the students had a felt panic when their teacher gave test. The last problem was the students felt afraid the teacher inform the score of the meeting. This study aimed to find out the speaking anxiety level at tenth grade SMAN 2 Lubuk Sikaping.The design of this research was a descriptive quantitative research.The population of this research were tenth grade students that consist of 134 students. The students were divided into four classes.The researcher took 25 % of the population by using random sampling technique to determine the sample because the population is more than one hundred students and there are 34 students of this research. To collect the data, researcher used questionnaire to find out speaking anxiety level of the students.The result researcher found the data there were 3 components of speaking anxiety. The consist of communication apprehension, test anxiety and fear of negative evaluation. It was found that 89 total score of the students had moderately low anxiety level in communication apprehension. Then 94 total score of the students had moderate anxiety level in test anxiety. The last result found that 88 total score of the students had moderately low anxiety level in fear of negative evaluation. In conclusion, the students speaking anxiety level at the tenth grade at SMAN 2 Lubuk Sikaping based on those three components above was 90 total score which mean the students anxiety level in speaking was in moderate level.